Maternal obesity and prenatal alcohol exposure are associated with child development: Results from the Safe Passage Study - Ayesha Sania; Shreya Rao; Nicolò Pini; Mandy Potter; Yael Rayport; Liana Eisler; Lucy Brink; Jyoti Angal; Michael M. Myers; Hein Odendaal; Amy J. Elliott; William P. Fifer; et al. (PLoS ONE, 2026)
A large body of evidence supports the role of the prenatal environment in shaping childhood development. The relative contributions of prenatal alcohol use (PAE), maternal socioeconomic, and nutritional status on child development vary in high- versus low-income settings. We analyzed data from a prospective cohort study among mother-infant dyads from Cape Town (CT), South Africa and the Northern Plains (NP), USA. The Mullen Scales of Early Learning were administered by trained assessors to evaluate cognitive, motor, and language development of 1-year old children. We used multiple linear regression models to assess standardized mean differences in development scores by (1) maternal prenatal factors, (2) delivery factors and (3) child factors within each study site. 1,728 infants from CT and 1,140 infants from the NP were included in the analyses. In CT, infants with moderate-to-high PAE had 0.17 SD (95% CI −0.30, −0.04) lower cognitive and 0.15 SD (−0.29, −0.2) lower expressive language scores compared to infants without PAE. In the NP, maternal obesity (BMI > 30 kg/m 2 ) was significantly associated with −0.21 SD (−0.36, −0.06), and −0.13 SD (−0.27, −0.02) reductions in cognitive, and expressive language scores, respectively. Household crowding, lower levels of maternal educational attainment, prenatal maternal depression, low birthweight, admission to neonatal intensive care unit, and male sex had significant negative associations with cognitive and language development in both sites with effects ranging from −0.32 to −0.11 SDs. These results highlight the importance of assessing risk factors by populations across diverse social and cultural environments and emphasize the imperative to formulate intervention packages tailored to the local context.